2006
DOI: 10.11606/issn.2448-1750.revmae.2006.89707
|View full text |Cite
|
Sign up to set email alerts
|

Human occupation and paleoenvironments in South America: expanding the notion of an “Archaic Gap”

Abstract: Uma revisão das informações arqueológicas produzidas no Brasil e países vizinhos durante as últimas décadas, aliada a uma análise de estudos paleoambientais recentes, sugerem que durante o Holoceno Médio amplas áreas da América do Sul deixaram de ser ocupadas por grupos humanos. Dados independentes, como datações de esqueletos humanos, estratigrafia de abrigos rochosos e cronologia de sítios arqueológicos a céu aberto convergem para a idéia de que tais áreas foram, no mínimo, fortemente depopuladas. Dados pale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 82 publications
0
12
0
5
Order By: Relevance
“…These new data are summarized in Table 2. Gruta do Gentio II is found at Unaí in the northwest of the state of Minas Geris, Central Brazil [23]. The cave is located in a calcareous bank 2.5 km long.…”
Section: Survey Findingsmentioning
confidence: 99%
“…These new data are summarized in Table 2. Gruta do Gentio II is found at Unaí in the northwest of the state of Minas Geris, Central Brazil [23]. The cave is located in a calcareous bank 2.5 km long.…”
Section: Survey Findingsmentioning
confidence: 99%
“…Paleoclimatologists concerned with reconstructing paleoenvironmental climatic changes in eastern Brazil during the Holocene have recently suggested that "humans might be regarded as good paleoenvironmental markers for the Holocene. In this light, we propose that archaeological data should be better explored, and regarded as a valuable basis for paleoenvironmental inferences" (Araujo et al 2005(Araujo et al /2006.…”
Section: Historical Ecology Versus Environmental "Determinism"mentioning
confidence: 99%
“…12,600 to 8500 cal BP 1 , and most sites are inside rockshelters. The occurrence of gaps in the human occupation of Lagoa Santa during the middle Holocene was acknowledged a decade ago (Araujo et al 2005, Araujo et al 2006, and the end of the Paleoindian occupation in the region was considered to be marked by the general abandonment of the rockshelters at 8500 cal BP.…”
Section: Introductionmentioning
confidence: 99%